Propuesta de una ruta agroturística en las parroquias Cariamanga y Chile del cantón Calvas, provincia de Loja - García Sarango, Stalin Aníbal (2018)
Ecuador due to its geographical location, it is one of the most megadiverse countries in the world due to its variety of climates and species diversity; this allows many people to come to our country. The southern highlands of the country and specifically the province of Loja has different places and cities when visiting, with a level of relevant importance in the tourism field that has been growing as time goes on. Calvas canton has tourism potential as it has attractions that are part of a set of options when it comes to distractions and relaxation. It is for all this that the established topic "Proposal of an agro-touristic route in the Cariamanga and Chile parishes in the Calvas canton, province of Loja", as well as a general objective: "To contribute to the tourist development through the design of an agro-touristic route in Cariamanga and Chile parishes of Calvas canton, province of Loja" With this objective it is intended to contribute to the tourist development of Calvas canton through the creation of an agro-touristic route, for which three specific objectives have been jointly established "Carry out a tourism diagnosis of the Cariamanga and Chile parishes of Calvas canton, Loja province." -To this end, the analytical method was used to analyze the tourist attractions that are part of the route. The inductive method was used as well, which has allowed to study the community and its degree of participation as well as to identify the way on the subject of culture, economy and social activity. In the same way, the direct observation technique and the interview technique were used; for the diagnosis, the methodology of Ricaurte (2009) was implemented, which includes of the communities and the characterization of the demand, for the ranking of the attractions the Minitry of Tourism cards were utilized, and for the diagnosis of the farms, a card was used which it was prepared based on the matrix of diagnosis attractions of Ricaurte (2009). For the collection of information of attractions, it was based on information the Land Management Plan of the GAD Calvas canton was used jointly to the FODA matrix was also carried out to obtain information on the analysis of the six internal elements of the tourism system, which are: Superstructure, Infrastructure, Demand, Attractions, Receiving Community and Equipment and facilities. The second objective was also proposed: "Elaborate the agro-touristic route in the Cariamanga and Chile parishes of the Calvas canton, province de Loja"- To achieve this objective, the synthetic method was used, through which it was possible to provide solutions for the dynamization of the tourism activity and identify the strengths, opportunities, weaknesses and threats of the elements of said activity by creating the route in the two parishes and therefore the development of the sector. Using the research carried out, materials tools were used for the design of the route as GPS for the taking of geographic coordinates, maps for georeferencing and creation of the route, for the proposal of the location of the signage supported in the manual of signage, the same that served for the correct location according to the needs and tourist activities, the use of technology was also essential for the design of the promotional and marketing material of the route. The third "Socialize the proposal of the agro-touristic route in the Cariamanga and Chile parishes of Calvas canton, Loja province.".- The deductive method was used, which allowed concluding with the criteria for the participation of the community and its and its consequent benefit of the route, the MARPP technique was used. "Cariamanga, agro-touristic and productive route" will contribute to the development of the Cariamanga and Chile parishes as well as the canton in general, since it will directly involve improving the economy, the farm owners and the tourist service providers as well as indirectly through the providers of additional services.